Kesiapan gen Z dalam mengelola keuangan di era Digital - Chitra Septiani; Hani Handayani; Vella Azahra Putri; Zauzia Siti Zahra; Hani Hatimatunnisani (LPPM Politeknik Pajajaran ICB, 2026)
Generation Z is an age group that grew up amidst the rapid development of digital technology. Easy access to information and various financial applications makes them very familiar with digital transactions such as e-wallets, mobile banking, and online investment. However, behind the adaptation of this technology, questions arise about the extent to which Gen Z is prepared to manage finances wisely and sustainably. This study aims to analyze the characteristics, behavior, and level of financial literacy of Gen Z in facing the challenges of the digital economy. The results of the analysis show that although Gen Z is active in using financial technology, they still have limitations in financial planning, risk management, and understanding of basic financial concepts. Therefore, increasing financial literacy through education and a digital media-based approach is an important strategy in forming a financially intelligent generation in the future. Keywords : Gen Z; Financial Management; Digital Era.